Examine the Role of Transformational Leadership in Entrepreneurial Orientation and Innovation: Explain the Mediating and Moderating Role of Learning-Orientation - Hamed Alipour, Mohammad Reza Zeinaddini, Iman Hakimi (International Journal of Advanced Science and Technology, 2019)
Understanding the needs and expectations of customers and responding to changes in the market plays a key role in organization’s success. For this purpose, it is inevitable to employ the introverted strategic orientations of entrepreneurship and learning orientation in organizations. Also, the need for continuous organizational change in today's dynamic and changing environmentsis the existence of visionary, strategic, or more clearly transformational leaders. Therefore, in this research, it is attempted to examine the relationship between transformational leadership, organizational entrepreneurship and innovation by examining the mediating and moderating role of learning orientation. This study was conducted in a sample of 368 senior managers of small and medium enterprises active in Iran’s food industry in 2016using a multi-stage cluster sampling method. The results of the analysis of the data collected with LISREL and PLS software show that the transformational leadership style, directly and indirectly through learning orientation, is a significant driving force in enterprise entrepreneurship orientation. Evidence also support the mediating role and lack of supportingthe moderating roleof learning orientation in the relationship between transformational leadership and entrepreneurship orientation in small and medium enterprises active in Iran’s food industry.